2019
DOI: 10.1186/s12895-018-0081-1
|View full text |Cite
|
Sign up to set email alerts
|

Differences in microRNA expression between melanoma and healthy adjacent skin

Abstract: BackgroundThe tumor microenvironment is composed of cancer-associated fibroblasts, tumor-associated macrophages, endothelial cells, immune cells, signaling molecules and extracellular matrix structures, which closelycommunicate with the tumor via multiple mechanisms. MicroRNAs are paracrine regulators that provide a direct interaction between the microenvironment and cancer cells. In the presentstudy, we aimed to identify the microRNA expression profile in melanoma compared with thatin healthy adjacent skin, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…MiR-146a-5p regulates several important cellular pathways like Toll-like receptor, NF-κB, and ErB. Actually, miRNA-146a-5p targets almost 40 genes, one of them being the well-known NRAS gene (Aksenenko et al, 2019). Prognostic miRNA tissue signatures that match the recent ones were reported several years ago.…”
Section: Tumor Microenvironment Mirna Expression In Cutaneous Melanomamentioning
confidence: 86%
“…MiR-146a-5p regulates several important cellular pathways like Toll-like receptor, NF-κB, and ErB. Actually, miRNA-146a-5p targets almost 40 genes, one of them being the well-known NRAS gene (Aksenenko et al, 2019). Prognostic miRNA tissue signatures that match the recent ones were reported several years ago.…”
Section: Tumor Microenvironment Mirna Expression In Cutaneous Melanomamentioning
confidence: 86%
“…In our present study, DEMs analysis found that miR-146a and miR-153b were both more highly detected in TM compared to those in WT. In mammals, recent studies have reported that miR-146a played an important role in melanoma [39,40,41] and retinal pigment epithelial cells [42]. Similarly, miR-153 could suppress cell proliferation and invasion by targeting snail family transcriptional repressor 1 (SNAI1) in melanoma [43].…”
Section: Discussionmentioning
confidence: 99%
“…Mi-RNA-146a has been previously incriminated in other malignancies, such as papillary thyroid cancer, hepatocellular carcinoma, or leukemia [62]. Mi-RNA-146a has also been involved in the pigmentation and survival of UM cells [63]. However, other studies did not support mi-RNA-146a as being a useful blood biomarker [56,64].…”
Section: Main Clinical Findingsmentioning
confidence: 99%